ICANN's dotCommunities: Analysing the construction of DNS-appropriate communities in the new gTLD programme. (January 2021) - Kuznetsov, Dmitry
This study investigates Internet Corporation of Assigned Names and Numbers' (ICANN) new generic top-level domain (gTLD) programme, exploring how it a shape of 'community' suitable for domain name system (DNS) expansion is constituted. Despite the apparent goal of promoting rights to freedom of expression and free association, the prevalence of the controlled vocabulary model results in preference for unopposed entities with clear hierarchical structures and strict membership boundaries. This creates a TLD landscape incapable of encompassing the heterogeneity and uncertainty of many existing communities, but helps to reinforce ICANN's discourse surrounding the function of the DNS and its role in Internet governance.